INOVASI PEMANFAATAN SAYURAN MENJADI SMOOTHIE DAN ICE CREAM SAYUR - Widayanti, Nila; Maimurni, Santa; Mulyadi, Dita Sari; Ratnasari, Noviana Dwi Putri; Aisyah, Siti; Syahria, Nukmatus (Jurnal Abadimas Adi Buana, 2018)
Vegetable is a way of traditional treatment of ancestral heritage that has long been known in Indonesia. Vegetable as a culture of the Indonesian Society desperately needs to be preserved. In an effort to preserve herbs and improve the benefits of herbal medicine in Indonesia, the Division of Work Program " Smoothies vegetable" KKN-PPM group in Kepuh Kemiri Village, Tulamgan made a new innovation in the form of herbal medicine in the form of smoothies. It aims to attract people to love more ancestral heritage products that are almost marginalized by modern market products lately. Through this new innovation, it is expected the interest of the community especially Kepuh Kemiri Village, Tulangan to herbal medicine can increase. Researchers use herbs as an ingredient of smoothies, because some people in the village of Kepuh Kemiri, Tulangan work as a maker of vegetable. This research activity was carried out in several hamlets in Kepuh Kemiri village, Tulangan namely RT.03 and RT.09 The KKM-PPM group activities in each sub-village are done by way of product socialization and how the product works. The results obtained from this research that there is a high interest from the community of Kepuh Kemiri village, Tulangan in making smoothies vegetable. It is expected that they can develop new innovations in the manufacture of vegetable so as to increase household income.